Tracing the reactivity of single atom alloys for ethanol dehydrogenation using ab initio simulations. Issue 1 (9th December 2021) - Iyer, Jayendran; Jalid, Fatima; Khan, Tuhin S.; Haider, M. Ali
Abstract : A full DFT parameterized MKM is used to accurately predict the reactivity trend for ethanol dehydrogenation reaction on SAAs. Abstract : An ab initio micro-kinetic model (MKM) is constructed to understand the reactivity trend of the single atom alloys (SAAs) of Cu and Au for non-oxidative dehydrogenation (NODH) of ethanol to produce acetaldehyde. The model utilizes well-known scaling relations between the transition state (TS) and final state (FS) structures to calculate product formation rates. The turnover frequencies (TOFs) of the product are plotted with respect to the two descriptors: carbon and oxygen binding energies on the catalyst surface. The resulting MKM has predicted no significant change in the activity of NODH on the NiCu SAA (TOF ∼ 10 −4 s −1 ) as compared to that on Cu (111) (TOF ∼ 10 −4 s −1 ). This stands in contrast to the experimental reports. A similar erroneous trend is calculated for NiAu, PtCu and PdCu SAAs using the scaling MKM. In parallel, an attempt is made to utilize a machine learning (ML) approach to augment descriptor prediction for the Cu based SAAs in the scaling MKM; however, the resulting trend remained similar and contradictory to experiments. The underlying reason for this discrepancy is unraveled in density functional theory (DFT) calculations of the NODH reaction over SAA surfaces, wherein a clear departure from scaling relations is observed, resulting in significant reduction in the activation barriers of the initial O–H or α-C–H activation steps in ethanol. Following which, a full-DFT parameterized non-scaling MKM is considered essential to estimate the reactivity trend of SAAs. Consistent with the experimental reports, the non-scaling ab initio MKM predicted the trend of the Cu based alloys as NiCu > PtCu ∼ PdCu > Cu at 400 K and Au based alloy as NiAu > Au at 500 K. The non-scaling MKM has further revealed the dominant mechanistic route for the NODH reaction via the initial O–H or α-C–H activation in ethanol. Except for PtCu, all other prominent SAAs (NiCu, PdCu and NiAu) are expected to follow the initial O–H scission route to produce acetaldehyde, while in the case of PtCu, both the mechanistic routes are likely to compete.